Platformization of Truth: Covid-19 Vaccination Discursive Groups on Twitter (Revista Brasileira de Pesquisa em Educação em Ciências, 2024)
This work discusses the relationship between the will for truth regarding COVID-19 vaccination and the different discursive groups in the so-called society of platform on Twitter. Specifically, this research is conducted through (1) understanding the network structure through Social Network Analysis and (2) evaluating the discourses of the groups based on the analytical concept of ‘plataformization of truth.’ Both the proposition of this concept and the contextualization of this research are rooted in Michel Foucault’s tools. Mixed methods are used to analyze the data collected on vaccination from December 2020 to January 17, 2021, on Twitter. Social Network Analysis was used to assess the composition of retweets on the topic, enabling the identification of antagonistic groups in the network. Subsequently, the concept of platformzation of truth is applied to qualify the content of a subset of the collected sample. The results indicate that two discursive groups were evident on the social network platform, with one cluster displaying an anti-vaccine stance and two clusters forming the pro-vaccine wing. The pro-vaccine wing employs different methods to disseminate the will for truth in favor of vaccination, with one group using humor and memes, and another group using predominantly scientific, journalistic, and/or political language. In the case of the anti-vaccine group, the discourse revolves around distrust of vaccines combating the coronavirus, especially CoronaVac. As a limitation, it should be noted that data collection is carried out from a segment of social media on a specific subject, which does not portray the entirety of the content present on the platform regarding that subject.